(untitled) (CANTING: Indonesian Community Development and Social Investment Journal, 2026)
Infaq and alms funds are distributed without interest (qardhul hasan) is a key instrument of Islamic philanthropy for transforming zakat recipients (mustahik) into zakat payers (muzakki), yet the monetary social value it generates is rarely measured systematically. This study assesses the social impact of the Petani Berdaya Program, a collaboration between Mandiri Amal Insani (MAI) Foundation and PT Mitra Desa Pamarican (PT MDP), which has channeled interest-free rice-farming capital to 178 smallholder mustahik farmers in Pamarican and Purwadadi Districts, Ciamis Regency, West Java, since January 2020. Applying the Social Return on Investment (SROI) framework of Social Value International, this evaluative study draws on primary data (observation, in-depth interviews, and focus group discussions with 67 informants) and secondary data for 2020–2022, complemented by a Logical Framework Approach (LFA) to design a program-strengthening strategy. Findings show SROI ratios of 1.13, 1.43, and 1.58 for 2020, 2021, and 2022 respectively, averaging 1.34 — meaning every IDR 1 invested generated IDR 1.34 of social value. Benefits were distributed across five stakeholders, with farmers as the largest beneficiaries (77.93%), followed by farmer groups (11.67%), PT MDP (7.19%), field facilitators (2.79%), and the agricultural insurer (0.42%). The 2022 decline was driven by brown planthopper and rodent attacks that fell outside the insurance coverage after the insurer’s quota was exhausted. The study recommends farm diversification through an Integrated Farming System, strengthening the off-taker function, written contracts for insurance and pricing schemes, and establishing a zakat, infaq, and sadaqah collection unit at the farmer-group level to accelerate the mustahik-to-muzakki transition.